Íñigo López de Mendoza, 4th duke of Infantado. A reader and a writer nobleman inside his humanist milieu - Carrasco Martínez, Adolfo (Cuadernos de Historia Moderna, 2019)
Íñigo López de Mendoza, IV duke of Infantado, was an avid reader and the author of Memorial de cosas notables (1564), dedicated to his dead heir. This paper focuses on the link between the duke and the arts and letters by studying his relationship with notorious humanists, as Juan de Vergara and Álvar Gómez de Castro, the family library, and the memory of his ancestor the marquis of Santillana. All of these items and activities were housed in the humanistic court he created inside his palace of Guadalajara. As a young man, Íñigo López was involved in the Guerra de las Comunidades, he was also engaged with the alumbrados, and he distanced himself from his father. These features could help us to understand his personality, his love for books and his cultural interest. As a duke, he had to face severe attacks against his authority from the Guadalajara’s council and above all, promoted by the crown. His library and his studies were his very true refuge.
Keywords: Íñigo López de Mendoza; 4th duque of Infantado; Castilian Humanism; Noblemen’s libraries; Noble patronage; Noble culture